The Influence of the FOMO (Fear of Missing Out) Phenomenon on Digital Community Participation on the Sidenreng Rappang Regency Government's TikTok Account as a Means of Public Communication - Aswan A.; Sapri; Herman Dema (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2026)
The digitalization of public services has encouraged government institutions, including the Sidenreng Rappang Regency Government, to use TikTok as an official communication channel through the @pemkab.sidrap account. This study aims to analyze the level of Fear of Missing Out (FOMO) among the public in accessing government TikTok content, assess the level of digital participation, and examine the effect of FOMO on digital participation. A quantitative approach was employed, involving 108 respondents selected from 4,371 followers using purposive sampling, followed by snowball sampling due to the absence of an accessible sampling frame on TikTok. Data were collected through an online questionnaire using a four-point Likert scale and analyzed using SPSS through descriptive analysis, validity and reliability tests, classical assumption tests, and simple linear regression. The findings indicate that FOMO has a positive and significant effect on public digital participation in the Sidenreng Rappang Regency Government’s TikTok account. This suggests that individuals’ desire to avoid missing information encourages them to access, follow, and interact more actively with government social media content. However, FOMO does not fully explain digital participation, as 31.7% of its variation remains attributable to other factors outside the research model. These findings highlight the relevance of psychological factors in understanding public engagement with digital government communication.